Canonic disabilities to marriage in genere - GÓRALSKI, WOJCIECH (Prawo Kanoniczne, 2012)
The subject of the author’s analysis are canonic disabilities to marriage, which are the subject of the second chapter of VII title: De matrimonio of Chapter IV of the Code of Canon Law; only the last part of this chapter has been omitted (devoted to dispensing disabilities), and this issue, due to its special character, requires a separate analysis. After explaining the concept, nature and functions of marriage breaking disabilities – in the context of ius connubbi (right to contract marriage) – a various typology of disabilities has been presented (among other, with regard to their origin and character), and, next, the Code principles of establishing and explaining these disabilities have been discussed, and, finally, the author focused on the institution of prohibition (vetitum matrimonii) The analysis of particular issues indicates, on one hand, on the fundamental significance of ius connubii in the system of the matrimonial canon law, and, on the other hand, the necessity to limit this law in due proportions, arising from concern in both dignity and sanctity of the institution of marriage itself and the church community, and parties contracting marriage.